Paul's summons to messianic life : political theology and the coming awakening - Welborn, L. L., 1953- (Insurrections., 2015)
Taubes, Badiou, Agamben, Zizek, Reinhard, and Santner have found in the Apostle Paul's emphasis on neighbour-love a positive paradigm for politics. By thoroughly reexamining Pauline eschatology, L.L. Welborn suggests that neighbour-love depends upon an orientation toward the messianic event, which Paul describes as the now time and which he imagines as awakening. Welborn compares the Pauline dialectic of awakening to attempts by Hellenistic philosophers to rouse their contemporaries from moral lethargy and to the Marxist idea of class consciousness, emphasizing the apostle's radical spirit and moral relevance.--